A Ferromagnetically Coupled (S=1) Peroxodicopper(II) Complex1. (21st December 2014) - Kindermann, Nicole; Bill, Eckhard; Dechert, Sebastian; Demeshko, Serhiy; Reijerse, Edward J.; Meyer, Franc
Abstract: Copper enzymes play important roles in the binding and activation of dioxygen in biological systems. Key copper/dioxygen intermediates have been identified and studied in synthetic analogues of the metalloprotein active sites, including the μ‐η 2 :η 2 ‐peroxodicopper(II) motif relevant to type III dicopper proteins. Herein, we report the synthesis and characterization of a bioinspired dicopper system that forms a stable μ‐η 1 :η 1 ‐peroxo complex whose Cu‐O‐O‐Cu torsion is constrained to around 90° by ligand design. This results in sizeable ferromagnetic coupling between the copper(II) ions, which is detected by magnetic measurements and HF‐EPR spectroscopy. The new dicopper peroxo system is the first with a triplet ground state, and it represents a snapshot of the initial stages of O2 binding at type III dicopper sites.